Studi Deskriptif Pemahaman Konsep Rangkaian Listrik Arus Searah Melalui Pembelajaran Laboratorium Riil dan Virtual - Tri Harry Indrah; Darsikin Darsikin; I Komang Werdhiana (Media Eksakta, 2021)
This study aims to describe the understanding of the concept of direct current electrical circuits through real and virtual laboratory learning. Subjects and respondents to this study as many as 6 students of the Physics Education Study Program class of 2016 who have programmed basic physics courses. The research instrument used is a three-tier multiple choice diagnostic test with DIRECT 1.1 which is a question of multiple choice with the reason in answering the question, each choice of answers accompanied by a choice of confidence level index in answering or CRI. The test instrument used as many as 24 question numbers. The test result data is then analyzed to determine the percentage of scientific concepts, understand alternative concepts, and do not understand concepts both before practicum and after practicum for each group. Based on the results of the analysis of research data, the concept of students before practicum either follow the learning through the real laboratory first then the virtual laboratory, as well as students who follow the learning through the virtual laboratory first then the real laboratory in the categorized very low, while after practicum in high categorization. Understanding the concept in students who have followed the learning using the real laboratory first then the virtual laboratory is relatively better compared to students who follow the learning using a virtual laboratory first then a real laboratory.